2011
DOI: 10.1093/cid/ciq152
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Risk Factor for a Novel Virus: Obesity and 2009 Pandemic Influenza A (H1N1)

Abstract: half of Californians ≥ 20 years of age hospitalized with 2009 H1N1 infection were obese. Extreme obesity was associated with increased odds of death. Obese adults with 2009 H1N1 infection should be treated promptly and considered in prioritization of vaccine and antiviral medications during shortages.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

18
304
5
13

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 400 publications
(340 citation statements)
references
References 35 publications
18
304
5
13
Order By: Relevance
“…We observed a higher risk of death among males, which has been reported previously for seasonal influenza 29 and has been attributed to numerous behavioral, immunologic and comorbid factors. 30 In our cohort, 93% of adults and 81% of children had underlying medical conditions While morbid obesity was a newly recognized risk factor for hospitalization and death from influenza during the 2009 pandemic 15,18 it was not associated with death in our study. Of note, an estimated 34.9% of all U.S. adults were obese during 2012 31 and roughly 50% of Californians ≥20 years of age hospitalized with 2009 H1N1 infection were obese.…”
Section: Discussionmentioning
confidence: 51%
See 1 more Smart Citation
“…We observed a higher risk of death among males, which has been reported previously for seasonal influenza 29 and has been attributed to numerous behavioral, immunologic and comorbid factors. 30 In our cohort, 93% of adults and 81% of children had underlying medical conditions While morbid obesity was a newly recognized risk factor for hospitalization and death from influenza during the 2009 pandemic 15,18 it was not associated with death in our study. Of note, an estimated 34.9% of all U.S. adults were obese during 2012 31 and roughly 50% of Californians ≥20 years of age hospitalized with 2009 H1N1 infection were obese.…”
Section: Discussionmentioning
confidence: 51%
“…Of note, an estimated 34.9% of all U.S. adults were obese during 2012 31 and roughly 50% of Californians ≥20 years of age hospitalized with 2009 H1N1 infection were obese. 15 In our cohort 48.0% of adult patients were obese; thus, obesity may still be a risk factor for severe influenza infection.…”
Section: Discussionmentioning
confidence: 70%
“…In a study on the pediatric age group, asthma and neurologic impairment were the most prevalent underlying risk factors (22). Regarding the role of obesity and being overweight, there are established evidences concerning the place of high BMI in severity of disease (19,23,24). In our study, BMI was shown to be an independent risk factor of Hypoxemia in the course of the 2009 pandemic influenza A (H1N1).…”
Section: Discussionmentioning
confidence: 50%
“…An association between a higher BMI and an increased risk of other viral infection such as influenza A and hepatitis C has been reported. 21,22 The secretion of cytokines from adipose tissue in obese patients may dysregulate the immune system, although the true mechanism remains unclear. 23,24 A prolonged cold ischemia time has been shown to increase the risk of ischemic cholangiopathy and subsequent allograft rejection.…”
Section: Discussionmentioning
confidence: 99%
“…The median age was 57 years (IQR, 47-62 years), and the sex distribution was almost equal. The median MELD score was 25 (IQR, [18][19][20][21][22][23][24][25][26][27][28][29]. The majority of patients were Caucasian (85%).…”
Section: Patient Characteristicsmentioning
confidence: 99%